Prognostic role of platelet to lymphocyte ratio in pancreatic cancers: A meta-analysis including 3028 patients. Issue 8 (February 2018) - Li, Wendi; Tao, Lianyuan; Lu, Meng; Xiu, Dianrong
Abstract: Background: Platelet to lymphocyte ratio (PLR) was recently reported being associated with the prognosis of pancreatic cancer (PC), but the prognostic value of PLR in pancreatic cancer remains inconsistent. We conduct a meta-analysis to evaluate the prognostic role of PLR in patients with PC. Methods: PubMed, Embase, Cochrane Library, and Web of Science were systematically searched for eligible studies which investigated the relationship between PLR and clinical outcome of patients with pancreatic cancer. Pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated to evaluate the prognostic role of PLR in overall survival (OS) and progression-free survival (PFS)/time to progression (TTP). Results: A total of 16 studies comprising 3028 patients with PC were enrolled in this meta-analysis. Pooled analysis demonstrated that elevated PLR predicted a poor OS (HR = 1.22, 95% CI: 1.09–1.36, P < .001). Prognostic role of PLR on OS were significant in subgroup of Asians (HR = 1.22, 95% CI: 1.11–1.34, P < .001), patients treated with chemotherapy (HR = 1.18, 95% CI: 1.04–1.35, P = .01) and mixed methods (HR = 1.29, 95% CI: 1.07–1.57, P = .009), American joint committee on cancer (AJCC) stage of III–IV (HR = 1.22, 95% CI: 1.09–1.36, P < .001), pathological subtype of pancreatic adenocarcinoma (HR = 1.21, 95% CI: 1.08–1.36, P = .001), and cut-off value of PLR ≥160 (HR = 1.48, 95% CI: 1.25–1.75, P < .001). Conclusions: An elevated PLR is associated with unfavorable overall survival in patients with pancreatic cancer.